Optimizing Tomato Plant Growth and Yield through Innovative Fertilizer Combinations: A Factorial Group Random Design Approach: Optimisasi Pertumbuhan dan Hasil Tanaman Tomat melalui Kombinasi Pupuk Inovatif: Pendekatan Rancangan Acak Kelompok Faktorial - Efendi, Muhammad Shofyan; Abror, M (Indonesian Journal of Innovation Studies, 2023)
This study employed a rigorous Factorial Group Random Design (RAK) method to investigate the synergistic effects of Liquid Complementary Fertilizer (PPC) and NPK Compound Fertilizer on the growth and yield of tomato plants. The research consisted of two key factors: PPC with four dosage levels (control, 3 g/L, 6 g/L, and 9 g/L of water) and NPK Compound Fertilizer with four levels (control, 200 kg/ha, 400 kg/ha, and 600 kg/ha) - all replicated three times. Data on critical plant parameters such as height, leaf count, flower abundance, and fruit production were meticulously gathered and analyzed. Remarkably, the combined application of PPC and NPK exhibited significant enhancements in both growth and yield, surpassing the effects observed from individual applications. Our findings highlight the immense potential of this innovative fertilizer combination in revolutionizing tomato crop production, offering a promising avenue for farmers to meet agricultural demands efficiently. Highlights: Utilized a robust Factorial Group Random Design (RAK) methodology to examine the impact of PPC and NPK Compound Fertilizer on tomato plant growth and yield. Investigated various dosage levels of PPC and NPK, each replicated three times for precise data analysis. The synergistic effects of the combined application outperformed individual applications, showcasing a promising approach to optimize tomato crop production. Keywords: Fertilizer Combination, Growth, NPK Compound Fertilizer, Tomato Plants, Yields